(untitled) (Academia Journal of Medicine, 2024)
Even if local anaesthetic remains the mainstay of pain management in dentistry, research will continue to hunt for innovative and more effective strategies to control the pain. The majority of research efforts are focused on developing anaesthetic medicines, delivery systems, and related approaches. Modern dentistry techniques enable dentists to provide better pain management with less painful injections and unfavourable side effects. The current review of the literature aims to compile persuasive evidence for dentists about the use of modern local anaesthetics, various techniques, and tactics to lessen pain while delivering anaesthesia and so enhance patient comfort.